Providing Behavioral Health Services in Nursing Homes Is Difficult: Findings From a National Survey. Issue 8 (5th June 2019) - Orth, Jessica; Li, Yue; Simning, Adam; Temkin‐Greener, Helena
Abstract : OBJECTIVES: Behavioral health (BH) disorders affect 65% to 90% of nursing home (NH) residents. Access to BH services in NHs has been generally considered inadequate, but the empirical evidence is sparse. We examined the availability of BH services and identified facility‐level factors associated with the difficulty of providing BH services in NHs. DESIGN: A national random sample of 3996 NHs was identified. Two structured surveys with questions about BH service availability, quality, satisfaction, staffing, staff education, turnover, and service barriers were mailed to administrators and directors of nursing in each NH between July and December 2017. SETTING/PARTICIPANTS: Completed surveys were obtained from 1079 NHs (27% response rate). Descriptive statistics and multivariable logistic regressions were employed. MEASUREMENTS: Four outcome measures were based on five‐point Likert scales: (1) adequacy of BH staff education; (2) ability to meet resident BH service needs; (3) adequacy of coordination/collaboration between NH/community providers; and (4) availability of necessary facility infrastructure. RESULTS: BH service needs were unmet in one third of NHs; almost half lacked appropriate staff BH education. Over 30% reported having inadequate coordination of care between NH and community providers, and 26.2% had inadequate infrastructure for residents' referrals/transport. Staff BH education was less problematic in NHs with Alzheimer disease units (odds ratio [OR] = 0.6; P < .05), lower registered nurse (RN) turnover (OR = 0.7; P < .05), and more psychiatrically trained RNs (OR = 0.5; P < .001) and social workers (OR = 0.6; P < .05). Lower RN turnover (OR = 0.7; P < .05) and more psychiatrically trained RNs (OR = 0.6; P < .05) were associated with fewer NHs reporting being unable to meet BH service needs. Having more psychiatrically trained RNs (OR = 0.6; P < .05) was associated with fewer NHs reporting inadequate coordination with community providers. CONCLUSION: Inadequate BH education and psychiatric training among NH staff were associated with subpar provision of BH services in this care setting. New initiatives that increase access to BH providers and services and improve staff education are urgently needed in NHs. J Am Geriatr Soc 67:1713–1717, 2019